IMPLEMENTASI KEBIJAKAN PP NOMOR 30 TAHUN 2019 TENTANG PENILAIAN KINERJA PEGAWAI NEGERI SIPIL (STUDI KASUS TENTANG PELAKSANAAN PENILAIAN KINERJA PEGAWAI NEGERI SIPIL DI SMP NEGERI 3 JEPON) - Widianto . (Master of Public Administration, Universitas Slamet Riyadi, 2022)
The number of employees who do not understand the mechanism aboutGovernment Regulation No. 30 of 2019, new regulations using the EmployeePerformance Goals and how to perform employee Performance Assessments sothat they cannot apply this regulation well. This study aims to analyze theimplementation of the Indonesian Government Regulation Number 30 of 2019concerning Civil Servants Performance for which his application has been begunin this year. The research method used qualitative research with descriptivemethod, informants amounted to 4 people and was selected based on purposivesampling. Data collection techniques include interviews, observations, anddocumentation. The results of the analysis show that, the implementation ofpolicies in the Civil Servants Performance Assessment has not been going well. Keywords: performance, communication, resources, dispoisi, bureaucracy